(untitled) (Ciudades, 2025)
This article presents a proposal of definition and methodology to study urban fragmentation in large Spanish urban areas. Defining fragmentation as the form, more or less concentrated or dispersed, that the unequal distribution of a group in urban space can take, we developed a methodology taking population born in the EU, Latin America, Asia and Africa residing in Madrid, Barcelona, Seville, Bilbao and Valencia according to Population Census 2001 and 2021 data by census section. The results show how by considering the intensity of the separation between groups (IS), the form of the separation (Moran Index) and the characterisation of census tracts on the basis of income (using data from Atlas de distribución de renta de los hogares), the most segregated groups are located, but also the most fragmented in areas with lower incomes. These results offer valuable information to study changes in the morphology of segregation in large Spanish cities and, therefore, in how to deal with the new mechanisms that affect the most vulnerable groups.